Bilateral Deep Peroneal Nerve Paralysis Following Kerosene Self-Injection into External Hemorrhoids - Khalil Rostami; Esmaeil Farzaneh; Hassan Abolhassani (Case Reports in Medicine)
Along with conventional therapies, some abrogated traditional treatment had been used for hemorrhoids like local Kerosene injection especially for extremely irritated external hemorrhoids. We report a rare case of Kerosene self-injection into the hemorrhoid. Despite antibiotics therapy, extent debridement, and colostomy, the patient died after 24 hours because of heart attack. Moreover, we discuss here the case with contact or injection of hydrocarbon materials and early care action to decrease the extensions of injury and side effects.